A Study on Coaching Culture and Workplace Performance with a Focus on Gender Diversity in IT Industry - Mohandas, Hema (Digital Repository of Theses, 2026)
This dissertation investigates the role of coaching culture in enhancing leadership development, improving employee performance, and advancing gender diversity in IT organizations. As organizations face increasing complexity and competition, coaching is emerging as a strategic tool for cultivating leadership capabilities and fostering inclusive workplace cultures. This research aims to explore the integration of coaching culture, particularly in terms of its impact on emerging women leaders and organizational outcomes. A qualitative approach was used, involving questionnaire instrument with business leaders, technology heads, HR enablers, learning and development (L&D) teams, culture audit team members and women leaders who had participated in coaching and leadership development programs. The findings demonstrate that coaching is pivotal in improving leadership effectiveness, particularly by enhancing self-awareness, emotional intelligence, and decision-making. Coaching programs aligned with organizational goals, especially those focused on diversity and inclusion (D&I), were found to be more effective in embedding coaching within company culture. The study highlights that coaching interventions tailored to women leaders effectively address barriers such as unconscious bias, imposter syndrome, and lack of senior mentorship, ultimately boosting their confidence and leadership skills. Participants reported improvements in performance, communication, and career progression following coaching, with many experiencing higher engagement scores and leadership effectiveness. Leadership sponsorship, particularly from senior leaders, was identified as a key enabler in the successful implementation of coaching programs. However, challenges such as resistance from senior leaders, inconsistent participation, and the need for long-term sustainability were noted. The research emphasizes that coaching culture must be continuously integrated into organizational practices, such as leadership development and performance management, to ensure lasting impact. This dissertation contributes to the understanding of coaching culture's role in organizational development, offering valuable insights for companies seeking to leverage coaching for leadership growth, performance enhancement, and gender equity. The study underscores the importance of strategic alignment, leadership commitment, and digital tools in scaling coaching initiatives for long-term success.